2017
DOI: 10.1007/jhep11(2017)189
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the TeV-scale mirage mediation with heavy superparticles

Abstract: Abstract:We discuss effective models derived from a supersymmetric model whose mediation mechanism of supersymmetry (SUSY) breaking is namely mirage mediation. In this model, light higgsino mass, that is required by the natural realization of the electroweak scale, is achieved by the unification of the soft SUSY breaking parameters at the low scale. Besides, we find that extra Higgs fields are also possibly light in some cases. Then, the effective model is a two Higgs doublet model (2HDM) with higgsinos, and i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 147 publications
0
6
0
Order By: Relevance
“…As an example, we showed that lepton flavor violation in the SUSY seesaw mechanism could have order reduction. The cancellation also works with the anomaly mediation and it is interesting to introduce the seesaw mechanism or vectorlike fields in the TeV scale mirage mediation models [43][47, [66][67][68][69][70][71][72] without spoiling its little SUSY hierarchy. There might be a plethora of other phenomenological applications including massive gauge bosons as in the grand unified theories.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, we showed that lepton flavor violation in the SUSY seesaw mechanism could have order reduction. The cancellation also works with the anomaly mediation and it is interesting to introduce the seesaw mechanism or vectorlike fields in the TeV scale mirage mediation models [43][47, [66][67][68][69][70][71][72] without spoiling its little SUSY hierarchy. There might be a plethora of other phenomenological applications including massive gauge bosons as in the grand unified theories.…”
Section: Resultsmentioning
confidence: 99%
“…In the minimal KKLT setup, α is a positive rational number [35,36]. In the literature, the phenomenology of positive α has been studied intensively particularly to resolve the fine-tuning problem to realize the electroweak (EW) symmetry breaking scale [40][41][42][43][44][45][46]. However, it is known that the muon g − 2 anomaly is hardly explained in the cases with positive α due to relatively heavy winos and bino.…”
Section: Mixed Modulus-anomaly Mediationmentioning
confidence: 99%
“…In the minimal KKLT setup, α is a positive rational number [61,62]. In the literature, the phenomenology of positive α has been studied intensively particularly to resolve the fine-tuning problem to realize the electroweak (EW) symmetry breaking scale [66][67][68][69][70][71][72]. However, the muon g − 2 anomaly is hardly explained in the cases with positive α due to relatively heavy winos and bino unless the other contribution exists [68,73].…”
Section: Jhep10(2021)064 2 Mixed Modulus-anomaly Mediationmentioning
confidence: 99%